(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The objective of this review article is to identify what has been researching about the teaching of Social Sciences in elementary school, based on the tracking of articles from journals derived from research, master’s and doctoral studies, in countries such as Spain, Mexico, Chile, Argentina and Colombia in the last five years. With this review, it was concluded that, the studies on the teaching of the Social Sciences are focused on didactic and historical aspects. Therefore, it is important to promote research that seek to investigate how the teaching of the Social Sciences in primary school is realized to have a global view of the object of study.